2022
DOI: 10.1002/trc2.12222
|View full text |Cite
|
Sign up to set email alerts
|

Including ethnic minorities in dementia research: Recommendations from a scoping review

Abstract: Introduction Ethnicity influences dementia etiology, prognosis, and treatment, while culture shapes help‐seeking and care. Despite increasing population diversity in high‐income settlement countries, ethnic minorities remain underrepresented in dementia research. We investigated approaches to enhance the recruitment, and consistent collection and analysis of variables relevant to, ethnic minorities in dementia studies to make recommendations for consistent practice in dementia research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 91 publications
3
25
1
Order By: Relevance
“…Findings from this review are consistent with prior reviews that have described solutions to increase representation of special populations in biomedical research, including among older individuals [3][4][5], minority populations [6,7], and women and children [8][9][10]. Importantly, only two existing reviews of which we are aware noted the importance of tailoring solutions to address particular social or institutional determinants of health that impact representation of special populations in biomedical research [11,12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Findings from this review are consistent with prior reviews that have described solutions to increase representation of special populations in biomedical research, including among older individuals [3][4][5], minority populations [6,7], and women and children [8][9][10]. Importantly, only two existing reviews of which we are aware noted the importance of tailoring solutions to address particular social or institutional determinants of health that impact representation of special populations in biomedical research [11,12].…”
Section: Discussionsupporting
confidence: 83%
“…Previous reviews have examined the factors that influence research participation and retention among underrepresented populations, yet much of this existing research has focused on a single population and solutions to increase representation in research, while few studies have focused on barriers to participation in biomedical research [3][4][5][6][7][8][9][10][11][12]. Further, while it is common to examine SDOH as risk factors for poor health that are external to health care or research, improving representation in biomedical research requires assessing and remediating the impact of SDOH on health, health care, and research inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…within health administrative data). The prevalence of studies in our review reporting procedures to increase enrolment of individuals from equity‐relevant groups (6%) compares poorly to a recent review of 66 (mostly observational) studies in dementia research which found that 37 (56%) reported on strategies to improve recruitment of racial and ethnic minorities 27 . Finally, the prevalence of trials reporting engagement with patients in our review (15%) is higher than in a previous review of clinical trials more generally 35 as well as in a broader sample of pragmatic trials in which less than 10% of trial reports mentioned patient or public engagement 36 …”
Section: Discussioncontrasting
confidence: 82%
“…Engagement with patients or other key stakeholders (e.g., knowledge users, community groups, decision‐makers) 25 has been demonstrated to enhance the relevance of clinical trials 26 and may draw attention to equity‐relevant considerations. 27 Therefore, in the first domain we also extracted whether the study reported any patient or other stakeholder engagement. If this was not explicitly reported, we reviewed the acknowledgments and author affiliations to determine whether any such stakeholders were acknowledged or included as co‐authors in the manuscript.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation